Legal Protection for LGBT People from Bullying Comments via Social Media - Ramadhan, Muhammad Fadhil Faiz; Michael, Tomy (International Journal of Social Sciences and Humanities, 2024)
Misuse of social media users and lack of knowledge can lead to crime in cyberspace. With the harassment via electronic media carried out by the perpetrator against the victim, the victim feels fear in itself. This research aims to find out how legal protection is for LGBT people from bullying comments via social media. The method used in this research is the normative juridical method with a conceptual approach and a statutory regulatory approach. The results of this research are that bullying comments made via social media towards LGBT people is a serious problem that must be addressed immediately. LGBT people in Indonesia do not have special protection from bullying. However, there are several provisions that can be used to protect LGBT people from bullying comments via social media, namely Article 436 of Law no. 1/2023 and Article 27 letter a of Law no. 1/2024. The lack of reporting and the still closed nature of our society regarding these criminal acts, makes every case of defamation through electronic media difficult to uncover. Therefore, it is necessary to study the legal protection for LGBT regarding bullying comments via social media as a form of criminal act which is the cause of bullying crimes which violate human rights.